Allelopathy potential of aqueous leaf extract of Mimosa ramosissima Benth. in germination and initial development of Panicum maximum cv. aruana and Amaranthus retroflexus L. (Research, Society and Development, 2020)
Allelochemicals are secondary substances capable of interfering in the germination, growth and initial development of other plants. In this sense, the study aimed to identify possible Allelopathy potential of aqueous leaf extract of Mimosa ramosissima Benth. in germination and initial development of Panicum maximum cv. aruana and Amaranthus retroflexus L. For this purpose, experiments with seven treatments and four replications were developed, being mimosa extract and the control.For each treatment 15 seeds were placed in Petri dishes with moistened filter paper with 15 mL of those extracts. All treatments were kept in a germination chamber at a temperature of 30 ºC and constant light. After 10 days of the experiment with P. maximum cv aruana and 7 days with A. retroflexus, the number of seeds germinated was counted, and the measurements of the size of the aerial and root parts of seedlings were performed. The data collected were analyzed based on the ANOVA analysis, Tukey test (P